2017
DOI: 10.1080/0361526x.2017.1309830
|View full text |Cite
|
Sign up to set email alerts
|

E-books for the Classroom and Open Access Textbooks: Two Ways to Help Students Save Money on Textbooks

Abstract: To help students withstand the rising cost of textbooks and in turn support the mission of student success, the University of South Florida (USF) has implemented two electronic resources-based initiatives as part of the Tampa Library's Textbook Affordability Project. Through the E-books for the Classroom program, the library purchases electronic versions of texts required for coursework, providing equitable access to needed materials at no cost to the students. For the past 5 years, this program has evolved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Studies found that students' opinions of e-books as helpful and simple to use had an influence on their intention to use the technology (Gelderblom, 2019, Nugroho et al, 2018. Boczar and Pascual (2017) affirmed that e-books aid students in completing their research, projects, and assignments. In a study on the effect of trust in mediating usefulness perception and ease of use in buying an e-book, Yudiarti and Puspaningrum (2018) reported that buyers accept e-books based on the perceived utility and ease of use.…”
Section: Ease Of Use Perception and Usefulness To Accept E-bookmentioning
confidence: 99%
“…Studies found that students' opinions of e-books as helpful and simple to use had an influence on their intention to use the technology (Gelderblom, 2019, Nugroho et al, 2018. Boczar and Pascual (2017) affirmed that e-books aid students in completing their research, projects, and assignments. In a study on the effect of trust in mediating usefulness perception and ease of use in buying an e-book, Yudiarti and Puspaningrum (2018) reported that buyers accept e-books based on the perceived utility and ease of use.…”
Section: Ease Of Use Perception and Usefulness To Accept E-bookmentioning
confidence: 99%
“…Licensed digital resources that are DRM-free can be used by many users simultaneously, in accessible formats, and with unlimited downloads or printing, which allows learners to retain materials after their course has ended while still adhering to copyright and fair use practice. Boczar and Pascual (2017) note that DRM-free e-books are "the model ebook we look for ideally" in their textbook affordability program (p. 99). Borchard and Magnuson (2017) also note publishers do not always offer electronic licenses for books available to the library in print, and many licenses are limited in use.…”
Section: Library Materials and Affordable Learningmentioning
confidence: 99%
“…Borchard and Magnuson (2017) also note publishers do not always offer electronic licenses for books available to the library in print, and many licenses are limited in use. Single-use licenses can function like a course reserve system (Boczar & Pascual, 2017;Borchard & Magnuson, 2017), but often have no time limit on use and therefore, can be unpredictably unavailable (Borchard & Magnuson, 2017).…”
Section: Library Materials and Affordable Learningmentioning
confidence: 99%
“…This has led to an increase in OER usage in the classroom resulting in enhanced use of interdisciplinary-instructional approaches and bridging educational gaps by employing a moral and ethical motive (De Langen & Bitter-Rijkema, 2012;Karppinen et al, 2019). The discussion around student affordability and pedagogical advancement has focused on statistical analysis of student retention and year-over-year inflation of for-profit textbooks creating a financial burden and stressors for students (Boczar & Pascual, 2017;Bonet & Walters, 2016). What this article attempts to accomplish is to highlight the creation of an OER and observe its practical use related to affordability and pedagogical advancement in the classroom.…”
Section: Introductionmentioning
confidence: 99%